ANALISIS EFISIENSI DAN PENGARUHNYA TERHADAP PERBAIKAN MANAJEMEN PERUSAHAAN - Mutiara Nugraheni (LPPM UNY, 2004)
Abstract This research located in “Warga Mulya” Milk Cooperation, especially inconcentrate production unit, where most of raw material was agricultural waste that acquired from outside Yogyakarta province. The objective of this research is to know efficiency analysis and it influence toward cooperation management improvement. Incooncentrate production related to technical efficiency and production cost, with expectation, it can be aroused Warga Mulya cooperation management and the other industrial ro implemented periodic evaluated of input allocating, so step of improvement and raising product process management can be do immediately, example for accuracy utilizing of material, machine and human resources. Data in this research analyzed were time series every month since 1993 through 2000. This research used approach production function type of Cobb-Douglas, while the estimated by Maximum Likehood Estimation (MLE) with Shazam version 6.2. production cost fuction used approach Cobb-Douglas type. Technical Efficiency Rate (TER) and alocative efficiency get from differential of production fuction. The result of this research indicated that the cooperation did not achieve an optimal technical and allocate efficiency. So that this cooperation have to do an improvement of management. Keywords: analysis, efficiency, mnagement